Responsabilidad extracontractual del Estado por desplazamiento forzado de personas. (2013)
Initially the theory of repairing the damage caused by act or omission attributable to the state as a subject faced the dogma of irresponsibility. This was a paradigm that in the context of the new constitutional law should not be allowed any validity because it is not a case of the exercise of a divine power or Leviathan because of its superiority over the inhabitants; as institutionalist theses of yore held. However; as it will be evident; there is some jurisprudence position that reminds us of those theses concerning the state responsibility because of the case of displaced persons and there are doctrinal realities that pose their attenuated return since the law of non-contractual liability appears as an option which is ill-suited for the victims. Hence the need to determine the pattern of resolution to the legal problem posed by the Administrative Justice in order to identify its characteristics and to establish the road map drawn to repair one of the most flagrant violations of human rights and humanitarian international law.